The Concept and Implementation of Mudharabah Contracts in Islamic Bank Financing Products - Kelompok 1, Sindy Wulandari; Chaerul Sani, Chaerul Sani; Wakiyah, Nurul Wakiyah; Arlin, M Jihad Arlin (Aghnina : Jurnal Hukum Ekonomi Syari'ah, 2025)
Islamic banking in Indonesia plays a significant role in promoting financial inclusion and economic development, particularly through the mudharabah contract. This contract represents a partnership between a fund owner (shahibul maal) and a fund manager (mudharib) based on a fair profit-sharing principle without involving riba. This study aims to explain the concept, implementation, and challenges in applying the mudharabah contract to Islamic bank financing products. Using a descriptive qualitative approach, the findings reveal that the mudharabah contract has two main forms, namely mudharabah mutlaqah and mudharabah muqayyadah, which provide flexibility in application according to customer needs. Islamic banks act not only as fund providers but also as business mentors. Challenges include loss risks, transparency issues, and limited public understanding of Sharia principles. With proper management, the mudharabah contract can serve as an effective solution for fostering Sharia-based economic growth and supporting the micro, small, and medium enterprise (MSME) sector.